Diffusion Tensor Imaging of the Kidney: Design and Evaluation of a Reliable Processing Pipeline - Borrelli, Pasquale; Cavaliere, Carlo; Basso, Luca; Soricelli, Andrea; Salvatore, Marco; Aiello, Marco (Scientific reports, 2019)
Diffusion tensor imaging (DTI) is particularly suitable for kidney studies due to tubules, collector ducts and blood vessels in the medulla that produce spatially restricted diffusion of water molecules, thus reflecting the high grade of anisotropy detectable by DTI. Kidney DTI is still a challenging technique where the off-resonance susceptibility artefacts and subject motion can severely affect the reproducibility of results. The aim of this study is to design a reliable processing pipeline by assessing different image processing approaches in terms of reproducibility and image artefacts correction. The results of four different processing pipelines ( eddy : correction of eddy-currents and motion between DTI volume; eddy - s2v : eddy and within DTI volume motion correction; topup : eddy and geometric distortion correction; topup - s2v : topup and within DTI volume motion correction) are compared in terms of reproducibility by test-retest analysis in 14 healthy subjects. Within-subject coefficient of variation (wsCV) and intra-class correlation coefficient (ICC) are measured to assess the reproducibility and Dice similarity index is evaluated for the spatial alignment between DTI and anatomical images. Topup - s2v pipeline provides highest reproducibility (wsCV = 0.053, ICC = 0.814) and best correction of image distortion (Dice = 0.83). This study definitely provides a recipe for data processing, enabling for a clinical suitability of kidney DTI.